2014
DOI: 10.3109/00952990.2014.920850
|View full text |Cite
|
Sign up to set email alerts
|

Propofol pretreatment induced place preference and self-administration of the tiletamine-zolazepam combination: implication on drug of abuse substitution

Abstract: These results suggest that tiletamine-zolazepam combinations might be used as a "substitute drug" by abusers of propofol. The careful use, dispensation, and monitoring of tiletamine-zolazepam combinations are advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…[12][13][14][15] The rewarding effects of tiletamine, zolazepam, and the tiletamine-zolazepam combination Our team has evaluated the abuse liability of the TZ combination and its constituents in the CPP and SA tests. Data from these experiments were analyzed using analysis of variance (ANOVA) followed by an appropriate post-hoc test.…”
Section: Methods Of Abuse Liability Assessment In Animalsmentioning
confidence: 99%
See 4 more Smart Citations
“…[12][13][14][15] The rewarding effects of tiletamine, zolazepam, and the tiletamine-zolazepam combination Our team has evaluated the abuse liability of the TZ combination and its constituents in the CPP and SA tests. Data from these experiments were analyzed using analysis of variance (ANOVA) followed by an appropriate post-hoc test.…”
Section: Methods Of Abuse Liability Assessment In Animalsmentioning
confidence: 99%
“…More details can be found in our previous studies. [12][13][14][15] The rewarding effects of tiletamine, zolazepam, and the tiletamine-zolazepam combination Our team has evaluated the abuse liability of the TZ combination and its constituents in the CPP and SA tests. [14] We found that the TZ combination produced neither CPP nor SA in drug-naïve rats.…”
Section: Methods Of Abuse Liability Assessment In Animalsmentioning
confidence: 99%
See 3 more Smart Citations